THE EFFECT OF DIET HABITS, PACKING, AND PRICE BARRIER ARE IMPACT ON ORGANIC FOOD PURCHASE BEHAVIOR - Hussain, Sajid; Zafar, Sohaib; Baqir, Muhammad (International Journal of Marketing Research Innovation, 2020)
Consumers purchase environmentally friendly products ‘’Organic food’’. This study is applied in Pakistan a country in which there is concern about safety and quality. The ‘’SEM’’ model is used to support our study. Three independent variables while one dependent variable is taken in that scenario. Data were obtained from 300 respondents, 278 backed us their response. We conclude from the above-mentioned model that the packing factor has much important than that of other variables. This sort of research can conduct in developed countries such as the US, CHINA, CANADA and other geographic areas. Also, green marketing factors can be replaced for future studies. Different independent variables contribute to future research like organic food labeling, lack of knowledge, and availability. We can also use different aspects such as environmental concern, health concern, and food safety concern using them as independent variables we can further use them in new research as a research gap. this research can also be done as longitudinal research.